EVALUATION OF POLYMER-COATED UREA TO REDUCE NITROGEN LOSSES IN SOIL AND ITS APPLICATION TO OKRA ABELMOSCHUS ESCULENTUS (L.) MOENCH - HASSAN, J; BADAR, S; KHAN, Z; HAYAT, U; KHAN, A; IJAZ, F; KHAN, ZA; SHERAZ, M; RASHEED, F; IQBAL, J (Biological and Clinical Sciences Research Journal, 2024)
The application of fertilizer aims to maximize crop yields and provide essential nutrients to plants. Efficiency problems, decreased yields, and environmental impact can result from nitrogen loss by volatilization and leaching. The delayed release of nitrogen can be achieved by coating urea with biodegradable compounds. The influence of several polymer-coated urea formulations and standard urea on nitrogen availability to okra plants was investigated in this study using lab and pot assessments. Key parameters were determined using soil samples taken at a depth of 15 cm. In the lab incubation, control, conventional urea, starch polymer-coated urea, neem oil-coated urea, and acacia gum-coated urea treatments were examined over 35 days. Soil samples were collected and examined on particular days. Okra plants were grown up to the flag leaf stage in the pot experiment using the same treatments. Data analysis demonstrated higher ammonium-nitrate and nitrate nitrogen concentrations in soils treated with polymer-coated urea, with acacia gum-coated urea exhibiting the slowest release. As release rates varied over time, nitrogen levels increased. Polymer-coated urea reduced ammonium loss, increased nutrient absorption, and boosted plant growth when compared to conventional urea. Urea with acacia gum coating functioned remarkably well, leading to increased nitrogen absorption. In conclusion, biodegradable polymer-coated urea increases nitrogen usage efficiency, decreasing losses and enhancing plant development, particularly when combined with acacia gum-coated urea. The results have practical significance for agricultural sustainability and the preservation of the environment.